L'économie solidaire en Bolivie. Entre marché et démocratie - Hillenkamp, Isabelle (KARTHALA Editions, 2013)
Depuis les années 1980, de plus en plus de pays ont opté pour une économie de marché et un régime politique de type démocratique et ce, indépendamment de leur « niveau de développement ». Pourtant, marché et démocratie ne sont pas directement compatibles. Si tous deux reposent sur les principes de liberté et d’égalité, le premier mise sur le pouvoir émancipateur du marché libre, alors que la seconde suppose une certaine égalité des conditions de vie. Une lecture croisée de cas européens et latino-américains illustre cette problématique commune, en même temps que la diversité des systèmes de médiations solidaires entre marché et démocratie. Les solidarités, qu’elles soient enracinées dans des structures familiales ou communautaires, instituées dans des systèmes de protection sociale ou organisées dans des groupes de producteurs ou de consommateurs de l’économie solidaire, créent en effet des interdépendances qui amortissent les tensions entre marché et démocratie. En développant cette analyse socioéconomique, Isabelle Hillenkamp propose une approche novatrice des questions de développement. Par des données récoltées auprès d’organisations d’économie solidaire et de nombreux autres acteurs en Bolivie, elle apporte des réponses ancrées dans la complexité d’un terrain de recherche. Isabelle Hillenkamp est titulaire d’un doctorat en études du développement de l’Institut de hautes études internationales et du développement, à Genève. A partir d’enquêtes en Amérique latine, ses travaux portent sur l’économie populaire et solidaire, qu’elle aborde dans une perspective socioéconomique, attentive aux liens entre pratiques économiques et rapports sociaux. Elle est chargée de recherche à l’Institut de recherche pour le développement, en France. Table des matières Introduction, L’économie solidaire en Bolivie, Entre marché et démocratie, Du pluralisme économique à la démocratisation I. Solidarité, marché et démocratie : une problématique européenne et latino-américaine II. Les organisations boliviennes d’économie solidaire : réciprocité et redistribution III. Les organisations boliviennes d’économie solidaire face aux marchés IV. Réciprocité, marché et démocratie : des tensions fondamentales V. La démocratisation de l’économie Ils en ont parlé Présentation du livre dans L'AGEFI, quotidien de l'Agence économique et financière à Genève Critique du livre sur le site Alterinfos, América Latina ENG translation: Since the 1980s, more and more countries have opted for a market economy and a democratic-type political regime, irrespective of their "level of development". Yet market and democracy are not directly compatible. If both are based on the principles of liberty and equality, the first is the emancipatory power of the free market, while the latter assumes a certain equality of living conditions. A cross-reading of European and Latin American cases illustrates this common problem, together with the diversity of solidarity-based mediation systems between market and democracy. Solidarity, whether rooted in family or community structures, instituted in social protection systems or organized in groups of producers or consumers of the solidarity economy, creates interdependencies that dampen tensions between the market and democracy. In developing this socioeconomic analysis, Isabelle Hillenkamp proposes an innovative approach to development issues. Through data collected from organizations of solidarity economy and many other actors in Bolivia, it brings answers anchored in the complexity of a field of research. Isabelle Hillenkamp holds a Ph.D. in Development Studies from the Graduate Institute of International and Development Studies in Geneva. Based on surveys in Latin America, her work focuses on the popular and solidarity economy, which she addresses in a socio-economic perspective, attentive to the links between economic practices and social relations. She is a researcher at the Research Institute for Development in France. Table of Contents Introduction, Solidarity Economy in Bolivia, Between Market and Democracy, From Economic Pluralism to Democratization I. Solidarity, Market and Democracy: A European and Latin American Issue II. Bolivian organizations of solidarity economy: reciprocity and redistribution III. Bolivian organizations of solidarity-based economy versus markets IV. Reciprocity, market and democracy: fundamental tensions V. The democratization of the economy They talked about it Presentation of the book in the AGEFI, the daily newspaper of the Economic and Financial Agency in Geneva Book review on the website Alterinfos, América Latina
Keywords: Bolivia; solidarity economy

From Economy to Society: Perspectives on Transnational Risk Regulation - Lange, Bettina; Thomas, Dania; Sarat, Austin (Emerald Group Publishing, 2013)
This special issue asks what role society can play in the regulation of transnational risks, as an alternative to or at least significant addition to reliance on state regulatory activity and the myth of the self-regulatory capacity of markets (Stiglitz, 2001, p. xiii). How can a social sphere contribute to the prevention and management of risks, often transnational in nature, posed by economic activity? Leading socio-legal scholars explore whether and how the idea of harnessing the regulatory capacity of a social sphere provides a new analytical lens that can provide fresh insights into transnational risk regulation, and whether this idea helps to identify innovative approaches to regulating transnational risks. KM - Parts I and II theoretically equgage specifically with Polanyi, and apply and develop Polanyian ideas.
Keywords: administrative law & regulatory practice; commercial law; comparative law; embeddedness; emotions; international law; international trade law; risk; self-regulating market

From the Great Transformation to the Great Financialization: On Karl Polanyi and Other Essays - Polanyi Levitt, Kari (Zed Books, 2013)
Four years into the unfolding of the most serious crisis since the 1930s, Karl Polanyi's prediction of the fateful consequences of unleashing the destructive power of unregulated market capitalism on peoples, nations, and the natural environment have assumed new urgency and relevance. Polanyi's insistence that 'the self-regulating market' must be made subordinate to democracy otherwise society itself may be put at risk is as true today as it was when Polanyi wrote. Written from the unique perspective of his daughter, From the Great Transformation to the Great Financialization is an essential contribution to our understanding of the evolution and contemporary significance of Karl Polanyi's work, and should be read against the background of the accelerating accumulation of global finance that created a series of financial crises in Latin America, Russia, Asia, and, eventually, the heartlands of capitalism itself.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Latin America; business & economics; economic conditions; economic development; economic history; global financial crisis; political economy; political science

Fortunes of Feminism: From State-Managed Capitalism to Neoliberal Crisis - Fraser, Nancy (Verso Books, 2013)
Charts the history of women’s liberation and calls for a revitalized feminism.Nancy Fraser’s major new book traces the feminist movement’s evolution since the 1970s and anticipates a new—radical and egalitarian—phase of feminist thought and action.During the ferment of the New Left, “Second Wave” feminism emerged as a struggle for women’s liberation and took its place alongside other radical movements that were questioning core features of capitalist society. But feminism’s subsequent immersion in identity politics coincided with a decline in its utopian energies and the rise of neoliberalism. Now, foreseeing a revival in the movement, Fraser argues for a reinvigorated feminist radicalism able to address the global economic crisis. Feminism can be a force working in concert with other egalitarian movements in the struggle to bring the economy under democratic control, while building on the visionary potential of the earlier waves of women’s liberation. This powerful new account is set to become a landmark of feminist thought.
Keywords: critical theory; feminism; feminist theory; triple movement

Towards an Economic Sociology of Law - Ashiagbor, Diamond; Kotiswaran, Prabha; Perry-Kessaris, Amanda (Wiley-Blackwell, 2013)
Reflecting a developing trend towards interdisciplinary research in economics and law, this agenda–setting volume makes the case for economic sociology of law  an emerging field that draws on empirical, analytical and normative insights from sociology to investigate relationships between legal and economic phenomena. It locates this novel subject in a wider socio–legal tradition and identifies common ground between Polanyian and Weberian approaches to the law, economy, and society, despite the two theorists  divergent views on the functionality of the capitalist model. The volume provides a platform for researchers critical responses to the social embeddedness of market societies. Contributors demonstrate the value of applying a combination of methods in their work, from heterogeneous disciplines such as legal history and ethnography. They consider the position in the western and developed nations, as well as in post–colonial polities. The resulting publication is a well–crafted primer on a specialism that, by combining the insights of socio–economic analysis with the formative influences exerted by their specific legal contexts, informs a more nuanced assessment of law, economics and society.
Keywords: WEBER, Max, 1864-1920; economic sociology; economic sociology of law; law

Commerce and Colonization in the Ancient Near East - Aubet, Maria Eugenia (Cambridge University Press, 2013)
In this analysis of the first colonialisms in history, the eastern roots of the Phoenician colonial system in the first millennium BC are traced and the metropolis of Tyre is established as the final link in a long chain of colonial experiences in the ancient Near East. The author reviews some of the theories and debates about trade and the colonial phenomenon, scrutinises the colonial situations that arose in the East in a context of long-distance interregional trade, and analyses the examples - Egypt, Byblos, Uruk, and Assur - where a metropolis with a mercantile tradition intervenes and acts as intermediary in different interregional exchange circuits. The success of a colonial metropolis is measured by its capacity to integrate dependent and complementary economies in circumstances where there is a strong demand for raw materials by the great powers. In that context, the profits obtained in the colonies thanks to price differentials between one region and another bring us back to the unending debate about the place of the economy in the ancient world and the pertinence of using features from modern economy - such as market, capital, private initiative, laws of supply and demand, and money - to explain the economies of the past.
Keywords: archaeology; business & economics; economic history; history / ancient / general

Karl Polanyi - Vail, John (Routledge Studies in Social and Political Thought, 2013)
Keywords: business & economics / economics / theory

Europe and Problems of Marketization: from Polanyi to Scharpf - Crouch, Colin (Firenze University Press, 2013)
The author uses the theory of the 'Great Transformation' of the industrialisation of England developed by Karl Polanyi to describe the current situation in Europe. There is a strong marketisation of the economy and also of social life, but what is missing is the social policy that needs to accompany this process, if there are not to be major problems. From this perspective marketization and social policy do not exist in a zero-sum game, but are mutually dependent. The emphasis on negative rather than positive integration (to use the terms conceived by Fritz Scharpf) in the development of Europe makes this interdependence more difficult to achieve. The division of competences between the European level (market policies) and the nation states (social policies) makes this situation even worse. The only way forward is a strengthening of the European social dimension.
Keywords: Europe; business & economics; commodification; economic theory; social policy

Socioéconomie et démocratie, l'actualité de Karl Polanyi - Hillenkamp, Isabelle; Laville, Jean-Louis (Toulouse : Érès éd, 2013)
La crise actuelle révèle des tensions fondamentales entre capitalisme et démocratie. L'orthodoxie occidentale, centrée sur les programmes d'ajustement, s'avère incapable d'affronter ce défi à la frontière de l'économie, du social et du politique. Il est temps de se tourner vers d'autres approches. S'appuyant sur l'oeuvre singulière de Karl Polanyi (1886- 1964) qui a décelé la dérive totalitaire de la société de marché, cet ouvrage soumet de nouvelles clés pour penser certains des problèmes les plus ardus de notre temps. Les auteurs, internationalement reconnus, venant d'Amérique et d'Europe, du Sud et du Nord, sont publiés pour la première fois ensemble en langue française. Ils proposent une vision croisée des rapports entre démocratie et économie, à partir de différentes disciplines et de divers terrains d'étude. Cette réflexion collective débouche sur la construction d'un cadre théorique permettant de comprendre la teneur des mutations économiques et politiques contemporaines. Mais elle ne s'arrête pas aux constats critiques. Face à la menace d'une régression autoritaire, elle s'intéresse aux pratiques qui concrétisent des issues solidaires et démocratiques à la crise. ENG: The aim of this book is to mobilize the contribution of Polanyi to think the socio-economy in a perspective of deepening democracy. The book updates the critical analysis of the new globalized capitalism but also identifies socio-economic experiences that can contribute to building more democratic societies in the 21st century.
Keywords: démocratie; développement économique - aspect social; economics - sociological aspects; triple movement; économie de marché; économie politique - aspect sociologique; économie sociale; économie sociale et solidaire